Bio-modified rubberized asphalt binder: A clean, sustainable approach to recycle rubber into construction. (15th April 2022) - Lyu, Lei; Pei, Jianzhong; Hu, Dongliang; Sun, Guoqing; Fini, Elham H.
Abstract: This paper introduces a hybrid utilization of scrap tires and bio-oil made from biomass waste to create bio-modified rubberized asphalt for use in roadway construction. This in turn promotes clean and sustainable manufacturing while enhancing resource conservation and durability of pavements. The durability of pavements is impacted by the resistance of their asphalt binder to moisture damage and aging. This study examines the moisture resistance of bio-modified rubberized asphalt when exposed to thermal aging and ultraviolet aging. Study results show that thermal aging significantly weakens the cohesive properties of rubberized asphalt binder, while ultraviolet aging reduces its adhesive properties when exposed to water. Bio-modification of rubberized asphalt binder was found to be effective to improve resistance to cohesive damage by three times based on the rheological test, and resistance to adhesive damage by 70% as measured by the moisture-induced shear-thinning index. The observed improvement is attributed to the bio-oil's role as a sacrificial agent, delaying the reaction of free radicals and asphalt. Also, computational modeling shows that bio-oil molecules supersede asphalt molecules in adsorption to stones aggregates creating a stable bridge between stone and asphalt. The outcome of this study promotes clean and sustainable manufacturing while turning two waste streams (rubber and biomass waste) into a product (bio-modified rubber) in support of resource conservation and sustainability. Graphical abstract: Image 1 Highlights: Water damage mechanisms in rubberized asphalt exposed to thermal and UV aging were examined. Biomolecules adsorbed to aggregates make a water-resistant bridge to asphalt. Bio-modification enhanced the cohesion and adhesion of rubberized asphalt.